2022
DOI: 10.1177/02676591221145646
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics, outcomes, and 30-day readmissions following pediatric extracorporeal membrane oxygenation in the United States: A Nationwide Readmissions Database study

Abstract: Objectives Extracorporeal membrane oxygenation (ECMO) is an increasingly used mode of critical care support for pediatric patients refractory to conventional therapy. We evaluated the characteristics, outcomes, and readmissions rates for pediatric ECMO in the United States. Methods Data was extracted from the Nationwide Readmissions Database, a database designed to support national readmissions analyses, for patients aged 1–18 years undergoing ECMO between 2012–2018. Baseline demographics, comorbidities, and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Eight studies reported improved survival in patients with private relative to government insurance (28, 77, 88, 89, 106, 123, 128, 129). Eight found no survival difference (55, 65, 81, 92, 130–133), with variable cost, complication, readmission, and LOS results (31, 33, 56, 70, 125, 126, 128, 134), including one with higher renal replacement in privately insured patients (83).…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies reported improved survival in patients with private relative to government insurance (28, 77, 88, 89, 106, 123, 128, 129). Eight found no survival difference (55, 65, 81, 92, 130–133), with variable cost, complication, readmission, and LOS results (31, 33, 56, 70, 125, 126, 128, 134), including one with higher renal replacement in privately insured patients (83).…”
Section: Resultsmentioning
confidence: 99%